2022
DOI: 10.1111/ppc.13131
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptoms and quality of life in women with polycystic ovary syndrome

Abstract: Purpose To determine depression symptoms and quality of life in women with polycystic ovary syndrome (PCOS). Methods The data were collected using the Participant Information Form, PCOS Quality of Life Questionnaire (PCOSQ‐50), and Beck Depression Inventory (BDI). The study was conducted with 131 women. Findings The average BDI score was found to be lower in women with PCOS who perceived their income as sufficient (p = 0.033) and who worked (p = 0.003) and was found to be higher in the participants who had hir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Another noticeable finding in this study was that having acne was a significant antecedent predictor of membership classification between the Complete Mental Health profile and Symptomatic but Content profile. Previous studies revealed that acne was significantly associated with an increased risk for anxiety and depressive symptoms (Kocak & Ugurlu, 2022). As shown by Ekramzadeh et al(Ekramzadeh et al, 2020), most PCOS women (90%) considered acne as one of the leading causes of fear, sadness, reduced self-confidence, and loss their physical attractiveness.…”
Section: Discussionmentioning
confidence: 94%
“…Another noticeable finding in this study was that having acne was a significant antecedent predictor of membership classification between the Complete Mental Health profile and Symptomatic but Content profile. Previous studies revealed that acne was significantly associated with an increased risk for anxiety and depressive symptoms (Kocak & Ugurlu, 2022). As shown by Ekramzadeh et al(Ekramzadeh et al, 2020), most PCOS women (90%) considered acne as one of the leading causes of fear, sadness, reduced self-confidence, and loss their physical attractiveness.…”
Section: Discussionmentioning
confidence: 94%
“…Some scholars have speculated that unique factors may be associated with psychiatric disorders of PCOS: such as illness perceptions, menstrual problems, unfulfilled wish to conceive, dissatisfaction with appearance and self‐image (e.g. obesity, acne, and hirsutism), fear of future health problems, and physical or emotional abuse 24,30,52,57–63 …”
Section: Resultsmentioning
confidence: 99%
“…obesity, acne, and hirsutism), fear of future health problems, and physical or emotional abuse. 24,30,52,[57][58][59][60][61][62][63] Hirsute women with PCOS had elevated odds of anxiety and depression, as well as lower quality of life and self-esteem scores. 44,64 Successful treatment of hirsutism, however, can lead to decreased scores of both depression and anxiety.…”
Section: Impact Of Pcos On Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…This study only identified that having acne was an important antecedent predictor of membership classification of mental health profiles among women with PCOS. The results of previous studies revealed that having acne was significantly associated with an increased risk for anxiety and depressive symptoms (Kocak and Ugurlu, 2022). As shown by Ekramzadeh et al (2020), most PCOS women (90%) considered acne as one of the leading causes of fear, sadness, reduced self-confidence, and loss of physical attractiveness.…”
Section: Discussionmentioning
confidence: 99%